The Impact of Contextual Teaching and Learning (CTL) Approach on Students in Learning English for Maritime at Indonesian Maritime Polytechnic - Nurlely Nasaruddin (Eduvest - Journal of Universal Studies, 2026)
This research was conducted to examine the significance of implementing the Contextual Teaching and Learning (CTL) model and its effects on students’ English for Maritime learning at the Indonesian Maritime Polytechnic. The study employed a descriptive research design, with data collected through observation, interviews, and documentation techniques. The collected data were analyzed using Miles, Huberman, and Saldaña’s interactive analysis model, which consists of data collection, data condensation, data display, and conclusion drawing. The results revealed that the implementation of the CTL model significantly influenced students’ learning motivation, participation, and comprehension of English for Maritime. The approach encouraged students to become more active, motivated, and collaborative by connecting classroom learning materials with real-world maritime contexts. Furthermore, the model enhanced students’ critical thinking, problem-solving abilities, and reflective learning practices, enabling them to apply knowledge actively rather than merely memorize concepts. The implementation of CTL also helped reduce students’ learning anxiety and improved their retention of maritime-related terminology.